Introduction to geotechnical engineering - Das, Braja M.; Sivakugan, N. (Cengage Learning, 2016)
Presents intensive research and observation in the field and lab that have improved the science of foundation design. Providing both US and SI units, this non-calculus-based book is designed for courses in civil engineering technology programs where soil mechanics and foundation engineering are combined into one course.